UPAYA PENINGKATAN KOMPETENSI GURU SMAN 1 TEBO DALAM MERANCANG RENCANA PELAKSANAAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK TAHUN AJARAN 2019/2020 - EMI RELI (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
This study aims to improve the continuous competence of teachers in preparing Learning Implementation Plans (RPP) through the implementation of academic supervision at SMA Negeri 1 Tebo for the 2019/2020 academic year. This research method is PTS (School Action Research). The study population used all teachers at SMA Negeri 1 Tebo as well as subjects in this study. The research instrument used a study of documentation, observation, and interviews. The data analysis technique used descriptive analysis. Based on the results of the study, it can be seen that continuous supervision is scientifically proven to be able to improve the continuous competence of teachers in preparing lesson plans at SMA Negeri 1 Tebo for the 2019/2020 school year. This is based on the results of research that shows an increase in data, namely by increasing the results of the assessment of the RPP from the pre-cycle which was only 26.67% (category